BIM-enabled Power Consumption Data Management Platform for Rendering and Analysis of Energy Usage Patterns. (2015) - Chiang, Cheng-Ting; Chu, Chun-Ping; Chou, Chien-Cheng
Abstract: Using a visualization engine to analyze power meter generated data about energy consumption of a building can provide immediate and informative feedback for energy conservation research. This paper proposed a platform, real-time replay system (RTRS), to provide such a visualized and interactive environment through the Unity 3d game engine. RTRS combines two data sources: Revit, a building information model (BIM) tool, and WiFi power socket sensors into Unity 3d and replays electricity usage events. RTRS users can easily change the scene or jump to the given time frame identified as a wasteful operation, and the system will display potential energy conservation suggestions. In addition, RTRS users can set up event triggering parameters or query conditions against the sensor database inside RTRS. In overall, RTRS can provide an intuitive and easy-to-use platform for managing electricity usage data of a building, reducing the time and efforts for looking up information at the raw data level.